2011
DOI: 10.1038/jcbfm.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Neuroprotection Provided by Inhibition of TRPM2 Channels following Experimental Stroke

Abstract: The calcium-permeable transient receptor potential M2 (TRPM2) ion channel is activated following oxidative stress and has been implicated in ischemic damage; however, little experimental evidence exists linking TRPM2 channel activation to damage following cerebral ischemia. We directly assessed the involvement of TRPM2 channels in ischemic brain injury using pharmacological inhibitors and short-hairpin RNA (shRNA)-mediated knockdown of TRPM2 expression. Each of the four TRPM2 inhibitors tested provided signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 44 publications
(50 reference statements)
7
135
2
Order By: Relevance
“…14 We confirm that important observation in this study using TRPM2 KO mice and neurons. Similarly, there is extensive evidence that inhibition of PARP-1 activity reduces ischemic injury in the male mouse brain specifically.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…14 We confirm that important observation in this study using TRPM2 KO mice and neurons. Similarly, there is extensive evidence that inhibition of PARP-1 activity reduces ischemic injury in the male mouse brain specifically.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we recently demonstrated that genetic knockdown (shRNA) or TRPM2 inhibition with clotrimazole (CTZ) reduced neuronal damage after middle cerebral artery occlusion (MCAO) or in vitro ischemia in male brain while having no effect in the female brain. 14,15 The aim of the current study is to determine the mechanism of TRPM2 regulation in the male brain.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Trpm2 deficiency in ischemic stroke has been suggested to preferentially protect neurons of male mice because of TRPM2 regulation by androgen signaling. 5,7,8 Although in vitro experiments point toward a central role of TRPM2 in neuronal injury, 6,9 its relative contribution to ischemic tissue injury in vivo by controlling immune cell activation has not been investigated. Notably, TRPM2 signaling controls specific functions in immune cells including production of cytokines and chemokines, chemotaxis of immune cells, and inflammasome activation.…”
Section: +mentioning
confidence: 99%
“…Therefore, TRPM2 might be involved in early ischemic neuronal cell death but also in the subsequent detrimental sterile inflammation. Involvement of TRPM2 in cerebral ischemic injury has recently been investigated, [5][6][7][8] showing a pathogenetic contribution of TRPM2 to ischemic stroke. However, these analyses focused on the role of TRPM2 in neuronal injury during ischemia.…”
Section: +mentioning
confidence: 99%
“…The activation of transient receptor potential melastatin (TRPM) channels, primarily the Ca 2+ -permeable TRPM2 (Lipski et al, 2006;Jia et al, 2011) and TRPM7 channels (Aarts et al, 2003;Sun et al, 2009), has been associated to oxidative stress, in addition to anoxic and ischemic cell death. Another key event during stroke is acidosis, caused by the decrease in the supply of oxygen to the brain, which leads to calcium influx, and failure of oxidative phosphorylation, with an increase in lactate production and the switch to glycolytic metabolism, with the final decrease in tissue pH (Xiong et al, 2004;Gu et al, 2010).…”
Section: Intracellular Calcium Overloadmentioning
confidence: 99%